2003
DOI: 10.1034/j.1600-6143.2003.30104.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of Anemia in Acute Renal Allograft Rejection Using DNA Microarrays

Abstract: Compromised renal function after renal allograft transplantation often results in anemia in the recipient. Molecular mechanisms leading to anemia during acute rejection are not fully understood; inadequate erythropoietin production and iron deficiency have been reported to be the main contributors. To increase our understanding of the molecular events underlying anemia in acute rejection, we analyzed the gene expression profiles of peripheral blood lymphocytes (PBL) from four pediatric renal allograft recipien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 25 publications
1
27
1
Order By: Relevance
“…It is also important for homeostasis of CD4 ϩ CD25 ϩ /CD4 ϩ CD25 Ϫ FOXP3 ϩ regulatory T cells (43) and TGF-␤-producing Th3 (44) cells that are known to have suppressive activity. The exact mechanisms driving and maintaining spontaneous tolerance in these patients yet remains unclear; however, there are data emerging about the diverse roles of tissue and peripheral TGF-␤ in protective (43) and injurious (45) alloresponses. The finding of increased expression of certain molecular markers of regulatory T cells in TOL patients over CR patients suggests differences in T cell subsets between these two groups.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important for homeostasis of CD4 ϩ CD25 ϩ /CD4 ϩ CD25 Ϫ FOXP3 ϩ regulatory T cells (43) and TGF-␤-producing Th3 (44) cells that are known to have suppressive activity. The exact mechanisms driving and maintaining spontaneous tolerance in these patients yet remains unclear; however, there are data emerging about the diverse roles of tissue and peripheral TGF-␤ in protective (43) and injurious (45) alloresponses. The finding of increased expression of certain molecular markers of regulatory T cells in TOL patients over CR patients suggests differences in T cell subsets between these two groups.…”
Section: Discussionmentioning
confidence: 99%
“…An increased inflammatory response including rejection seems to downregulate genes that are involved in erythropoiesis (29). It has also been shown that in patients who return to hemodialysis after graft failure and who undergo nephrectomy have a lower high-sensitivity C-reactive protein level and lower requirements for rh-EPO with higher hemoglobin levels than in patients who have returned to hemodialysis but did not undergo nephrectomy (30).…”
Section: Causes and Correlatesmentioning
confidence: 99%
“…As to kidney transplant, various reports have emphasized the capacity of microarray technology to find genes and elucidate molecular pathways that are involved in the progression of renal allograft damage (16)(17)(18)(19)(20)(21). Identification of prognostic factors in the transplantation setting may lead to the development of improved intervention strategies and may contribute to a better understanding of the pathophysiology of CAN.…”
mentioning
confidence: 99%